Foundationalism in ethics from the perspective of Ayatollah Javadi Amoli; review and explanation - majid abolqasemzade (اخلاق وحیانی)
The existence of self-evident theorems and the referral of theoretical theories to them (foundationalist theory) are among the important issues of epistemology. What is their improvisation? Can the science of ethics prove its theoretical propositions with little self-evidentness and is unnecessary to other sciences? The correct analysis of such issues has a great impact on defending moral values ​​and responding to its inequalities, especially relativism and moral pluralism. This text, by way of descriptive-analytical approach and by referring to all of his works, has come to the conclusion that there is an axiom in ethical science that is self-evident in its originality and conscience; That the science of morality is completely unnecessary from other sciences. There are some ambiguities that seem inconsistent at the outset.